1990
DOI: 10.1002/ange.19901021206
|View full text |Cite
|
Sign up to set email alerts
|

Die Porphyrin‐Homologen: [22]Porphyrin (2.2.2.2), ein „gestrecktes Porphycen”︁

Abstract: Atome von der mittleren Ringebene: 0.07 A). Aus der Symmetrie folgt, dab die einander gegeniiberliegenden C,,2C,,C,,C,p,-Struktureinheiten aquivalent sind und somit 12 als Resonanzhybrid zu formulieren ist. Was die geometrischen Parameter der genannten c,-Einheiten betrifft, so besteht sowohl hinsichtlich der Bindungswinkel an den sp-hybridisierten Kohlenstoffatomen (178.8 und 177.1") als auch in Bezug auf die Langen von C,,,C,,-und C,,C,-Bindungen (1.385 und 1.387 8, bzw. 1.21 7 A) vorziigliche Ubereinstimmun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

1990
1990
2007
2007

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 26 publications
(12 citation statements)
references
References 42 publications
0
12
0
Order By: Relevance
“…The results obtained, taking into account the major compound obtained, mainly depend on the nature of the electrophile used (Scheme 2) [129,130,[132][133][134]140,141]. Compounds (17, R 1 =H, n-Pr) and (20, R 1 =n-Pr) were used for a further derivatization of the porphycene ring [129,130,132]. Acetoxylation of the porphycene ring was achieved by treatment of (1, R 1 =H) and (1, R 1 =n-Pr, (CH 2 ) 2 OMe) with lead tetraacetate to give the corresponding 9-acetoxyporphycene (24, R 1 =H, n-Pr, (CH 2 ) 2 OMe) [129,130,132], which opened the gate to 9-Modification of the core structure of porphycene has been carried out by different approaches: (a) synthesis of structural isomers, (b) fusion with benzene rings, and (c) heteroatom substitution.…”
Section: Peripheral Functionalization 233 Modification Of the Corementioning
confidence: 99%
See 4 more Smart Citations
“…The results obtained, taking into account the major compound obtained, mainly depend on the nature of the electrophile used (Scheme 2) [129,130,[132][133][134]140,141]. Compounds (17, R 1 =H, n-Pr) and (20, R 1 =n-Pr) were used for a further derivatization of the porphycene ring [129,130,132]. Acetoxylation of the porphycene ring was achieved by treatment of (1, R 1 =H) and (1, R 1 =n-Pr, (CH 2 ) 2 OMe) with lead tetraacetate to give the corresponding 9-acetoxyporphycene (24, R 1 =H, n-Pr, (CH 2 ) 2 OMe) [129,130,132], which opened the gate to 9-Modification of the core structure of porphycene has been carried out by different approaches: (a) synthesis of structural isomers, (b) fusion with benzene rings, and (c) heteroatom substitution.…”
Section: Peripheral Functionalization 233 Modification Of the Corementioning
confidence: 99%
“…The subsequent acylation (Y=alkyl) [85,123] or formylation (Y=H) [62,66,124,125] of 3 and 4 using the Vilmeier-Hack protocol (YCONMe 2 /POCl 3 ) finally yields 5,5'-diacyl (Y=alkyl) and 5,5'-diformyl substituted (Y=H) 2,2'-bipyrroles (2), which are the immediate precursors of 2,7,12,17-tetrasubstituted porphycenes (1, Y=H, R 2 =H), 2,3,6,7,12,13,16,17-octasubstituted porphycenes (1, Y=H) and 9,10,19,20-tetrasubstituted porphycenes (1, R 1 =R 2 =H). This methodology has been claimed to be of general applicability, and several patents [129][130][131][132][133][134][135][136] have been filed covering a wide range of substituents R 1 , R 2 , and Y. A search carried out in SciFinder Scholar 2006 revealed that the total number of porphycene structures included in Chemical Abstracts is 239, their substituents mainly being of alkyl type.…”
Section: The Ideal Pdt Sensitizermentioning
confidence: 99%
See 3 more Smart Citations